ENVIRONMENTAL SAFETY TECHNOLOGY ON SCRAP TIRES TREATMENT - Vovk, Oksana A.; Nikitchenko, Julia S. (Proceedings of National Aviation University (archive), 2009)
This article is devoted to the problem of scrap tires treatment. The appropriate technology of tires pyrolysis and physical-chemical analysis of liquid hydrocarbons, which are usually obtained in the process of thermal destruction of wastes are considered. Main aim of this analysis is the comparison of liquid fraction characteristics with traditional fuels (petrol, diesel, kerosene) in order to show that this pyrolysis product could be identified like an alternative motor fuel.